POLA ASUH DEMOKRATIS ORANG TUA DALAM MEMBERIKAN MOTIVASI BELAJAR SISWA SELAMA MASA PANDEMI COVID-19 - Ainur Rohmania; Deka Setiawan; Khamdun (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine how parents applied democratic parenting patterns in providing learning motivation for students of SD Negeri 2 Rajekwesi Mayong Jepara duringthe covid-19 pandemic. This study discussed how the democratic parenting style of parents motivated the children to learn. This study used a qualitative method with a case study approach. The subjects in this study were students and their parents. Data collection techniques used were observation, interviews, and documentation. The data analysis used was descriptive data analysis. The results showed that during the covid-19 pandemic, the democratic parenting pattern was applied by parents to motivate children’s learning by encouraging and supporting the children, accompanying the children while studying, rewarding children, and giving positive advice. Based on the result of the study, it was concluded that the democratic parenting style was very influential in providing learning motivation for students of SD Negeri 2 Rajekwesi during the covid-19 pandemic.